Chinese Sweatshops: The Result of Outsourcing by Global Business Giants - Majumder, Indrani (Prabandhan: Indian Journal of Management, 2008)
Everywhere on this earth where there was enormous surplus, perhaps the ultimate destination of desperate workers were the sweatshops. It has its origin between 1830 and 1850: A special kind of workshop where a middleman, "the sweater", directed the workers in garment making "under arduous conditions" was termed as sweatshops. To fulfill their minimum basic needs, the workers aggressively went there as they had no other way. Analysts sometimes used it to describe a workplace which was "physically or mentally abusive, or that crowds, confines, or compels workers, or forces them to for work long and unreasonable hours, as would be the case with penal labor or slave labor". Charles Kingley in his writing 'Cheap Clothes&Nasty' in 1850 used the term "sweater" for the subcontractor and "sweating system" for the process they did their business. It was the National Labor Committee which brought the sweatshops "into the mainstream media".